Audience sentiment analysis of Fujianti Utami Putri’s endorsement on Nuface Skincare sales on the TikTok platform - Rika Septia Andriani; Dani Fadillah (Universitas Ahmad Dahlan, 2026)
Advances in digital technology, particularly social media platform like TikTok, have transformed marketing strategies into more interactive approaches through the use of influencer. One notable phenomenon is the endorsement of skincare products by Fujianti Utami Putri, which has the ability to influence audience perceptions and behavior. This study aims to analyze audience sentiment toward Nuface product promotions on TikTok and identify the factors influencing these responses. The method used is a qualitative approach involving content analysis of audience comment on three videos with the highest interaction rates during the July-September 2025 period. Data was collected using purposive sampling and analyzed through the classifications of positive, negative, and neutral sentiments. The results indicate that positive sentiment dominates audience responses (Up to 90%), followed by neutral sentiment and very little negative sentiment. The main factors influencing positive sentiment are the authenticity of communication, the influencer credibility, and the emotional closeness formed through parasocial interaction. The implications of this study emphasize that the success of digital marketing depends not only on product quality but also on the influencer ability to build trust and foster emotional engagement with the audience, thereby serving as an effective strategy to boost purchasing interest in the digital era.